UPAYA PENINGKATAN KINERJA PEGAWAI KANTOR KECAMATAN PEJAGOAN KABUPATEN KEBUMEN - Haryadi, Madep; Chasanah, Uswatun (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
The purpose of writing this thesis is to find out what strategies are appropriate for improving employee performance, while the benefit of this writing is to enrich the knowledge of human resource management for improving performance, especially in Pejagoan District, Kebumen Regency. Apart from that, as input material to find out the extent of success achieved in an effort to provide services to the community as a means of comparing knowledge and enriching information regarding improving employee performance in other research. The method used is a qualitative method. The data sources used are primary and secondary data, while the techniques used in data collection are documentation, interviews and observation. Based on the results of research, efforts have been made to improve employee performance in Pejagoan District by increasing human resources, both quality and quantity, in Pejagoan District. Improving facilities and infrastructure, both office equipment and office buildings. Implementing a reward and punish system for employees to more effectively carry out their respective main duties and functions.